Mirrored in God': Gramsci, Religion and Dalit Women Subalterns in South India - Kapadia, Karin (Religions, 2019)
The Tamil Dalit Pentecostal conversion movement that has been active in Chennai's slums and low-income settlements for the last four decades is also a political movement. It is, moreover, a women's political movement. Normally both Dalits and women are ignored in India, they are considered people of no importance and irrelevant to the issues that grab the headlines. But it is important for us to recognize both the political nature and the importance of this Dalit women's conversion movement, because we are at a time of great peril in India, where, as elsewhere, populist nationalism has swept an authoritarian leader to power and the fascist tendencies of an overbearing state are becoming increasingly obvious. In such a context Gramsci's theorizations provide important suggestions for how to understand religio-cultural movements as political movements and how to evaluate both their importance and what they can teach us about the possibilities for religio-cultural-political resistance to authoritarian populism, and the crucial importance of low-income, low-status women in political processes of grassroots resistance.